2006
DOI: 10.1007/s10194-007-0320-4
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life among Canadians with migraine

Abstract: The objective was to determine the impact of migraine on health-related quality of life (HRQOL) among Canadians. Analysis was based on the public use microdata set of the Canadian Community Health Survey (CCHS), limited to those aged ≥5 residing in Manitoba. HRQOL was measured using the SF-36 survey, which covers 8 health concepts. Multivariate linear regression was used to model each SF-36 scale against age, gender, education, income, migraine status and presence of mood or anxiety disorders. Of the 7236 CCHS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 14 publications
3
12
0
Order By: Relevance
“…Additionally, our results build upon previous findings of reduced HRQOL in subjects when migraine was comorbid with depression as compared to migraine alone (37), and a later study which reported that individuals with migraine comorbid with mood disorders had lower HRQOL in all domains with pronounced effects on emotional role, social functioning and general health in comparison to those with migraine alone (38). Although there was a decline in health perception and an increase in health utilization with increasing physical or mental comorbidity, the most intriguing result is the greater influence of comorbid mental, as opposed to physical, conditions.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, our results build upon previous findings of reduced HRQOL in subjects when migraine was comorbid with depression as compared to migraine alone (37), and a later study which reported that individuals with migraine comorbid with mood disorders had lower HRQOL in all domains with pronounced effects on emotional role, social functioning and general health in comparison to those with migraine alone (38). Although there was a decline in health perception and an increase in health utilization with increasing physical or mental comorbidity, the most intriguing result is the greater influence of comorbid mental, as opposed to physical, conditions.…”
Section: Discussionsupporting
confidence: 86%
“…Previous authors suggested that depressive symptoms may have detrimental effects on QoL of patients with migraine. However, in the majority of previous studies, QoL was assessed by clinical instruments not specifically designed for this specific population, such as SF-36 or SF-12 [6,7,[16][17][18]. Moreover, several prior studies focused on the presence of some psychiatric symptoms without considering a structured syndromical approach.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, depression has been associated with the occurrence of migraine, 2 where people who suffer from depression are 3 times more likely to also suffer from migraine 30 . The association between childhood physical abuse and anxiety has also been well established, 6,10 as has the association between anxiety and migraine 3,46‐48 . It should be noted that in several studies, patients with comorbid depression and anxiety were more likely to have migraine than patients suffering from only one condition 3,46,48 …”
Section: History Of Mood And/or Anxiety Disordersmentioning
confidence: 97%